Microstructure and Tribological Properties of Laser Cladding NiCrMo and NiCrBSi Alloy Coatings - CAO Si - long, WANG Ling - qian, ZHOU Jian - song (Cailiao Baohu)
At present, there are few reports on the high temperacture tribological behavior and mechanism of NiCrMo alloy coatings, for this, NiCrMo and NiCrBSi alloy coatings were prepared by laser cladding technology. The NiCrBSi alloy coatings, which were widely studied and widely used, were used as a contrast. The phase composition, microstructure, worn morphology and composition of the coatings were analyzed by X - ray diffraction, scanning electron microscopy and Raman characterization. The main wear mechanism of this two coatings was investigated from room temperature to 800 ℃. Results showed that the microstructure of NiCrMo alloy coating was mainly composed of fine dendrites formed by a single γ - Ni solid solution. The small atoms B, Si and C in NiCrBSi alloy coating were mainly distributed in γ - Ni solid solution in the form of Cr7C3 hard phase and Ni - B - Si eutectic structure. From room temperature to 400 ℃, NiCrMo alloy coating had serious abrasive wear and plastic deformation. NiCrBSi alloy coating possessed higher microhardness and plastic deformation resistance, committing to better wear resistance. When the temperature was over 400 ℃, the hard particles formed by fatigue shedding of Cr7C3 hard phase and Fe2O3 aggravated the cutting damage to the oxide film, which led to serious abrasive wear of NiCrBSi alloy coating under high temperature. However, a large amount of metal oxides and NiMoO4 complex on the worn surface of NiCrMo alloy coating could form a continuous and compact oxide enamel film, which reduced the friction and wear rate, and thus NiCrMo alloy exhibited better wear resistance at high temperature.